2017
DOI: 10.1515/forj-2017-0010
|View full text |Cite
|
Sign up to set email alerts
|

Soil biodiversity and environmental change in European forests

Abstract: Biodiversity not only responds to environmental change, but has been shown to be one of the key drivers of ecosystem function and service delivery. Forest soil biodiversity is also governed by these principles, the structure of soil biological communities is clearly determined by spatial, temporal and hierarchical factors. Global environmental change, together with land-use change and forest ecosystem management, impacts the aboveground structure and composition of European forests. Due to the close link betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 52 publications
(51 reference statements)
1
8
0
Order By: Relevance
“…Extensive (ie low-input) management, as practiced in the dry pastures of the Val Mazia/Matschertal LTSER area, supports the development of a distinct and specialized community (Steinwandter et al 2019), as has been shown in a recent multi-taxon study including above-and belowground taxa (Hilpold, Seeber, et al 2018). Even though we could not confirm this for the soil macroinvertebrate community, since the dry pastures showed the lowest abundances and the fewest species compared to the other 3 land use types, this recommendation still holds, since aboveand belowground biodiversity are closely connected and affect each other (Bardgett and van der Putten 2014;Lukac 2017). We assume that the low numbers are connected primarily to abiotic (ie shallow, hot, and dry soils) and not to land use parameters.…”
Section: Discussionsupporting
confidence: 52%
“…Extensive (ie low-input) management, as practiced in the dry pastures of the Val Mazia/Matschertal LTSER area, supports the development of a distinct and specialized community (Steinwandter et al 2019), as has been shown in a recent multi-taxon study including above-and belowground taxa (Hilpold, Seeber, et al 2018). Even though we could not confirm this for the soil macroinvertebrate community, since the dry pastures showed the lowest abundances and the fewest species compared to the other 3 land use types, this recommendation still holds, since aboveand belowground biodiversity are closely connected and affect each other (Bardgett and van der Putten 2014;Lukac 2017). We assume that the low numbers are connected primarily to abiotic (ie shallow, hot, and dry soils) and not to land use parameters.…”
Section: Discussionsupporting
confidence: 52%
“…Crucial to healthy soils is their biological component, represented by the wide range of organisms present in soils (Bardgett and Van Der Putten, 2014). This soil biodiversity highly contributes to the delivery of forest ecosystem services through the ecosystem functions that they fulfil in a complex soil food web (Bardgett and Van Der Putten, 2014;Lukac, 2017;Mori et al, 2017). Despite their crucial role, soil biodiversity and soil biological functioning are currently under pressure, especially in agricultural areas (Orgiazzi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their crucial role, soil biodiversity and soil biological functioning are currently under pressure, especially in agricultural areas (Orgiazzi et al, 2016). While forest soil biodiversity experiences mostly moderate risks, maintaining and optimizing its current level is crucial, as forests take up circa 40% the European Union's land area and are believed to play an essential role in climate change mitigation and future delivery of a wide range of ecosystem services (Eurostat, 2019;Gardi et al, 2013;Lukac, 2017). Orgiazzi et al (2016) categorized the origin of pressures on soil biodiversity in Europe into 13 categories, the majority of which are directly (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil biota is highly diverse, representing 23% of the described organism diversity (Decaëns et al, 2006). Forest soil biodiversity responds to environmental changes and has been shown to be one of the key drivers of ecosystem function and service delivery (Lukac et al, 2017). An important component of soil biota is represented by soil macrofauna (Lavelle, 1997).…”
Section: Introductionmentioning
confidence: 99%